2020
DOI: 10.15184/aqy.2020.140
|View full text |Cite
|
Sign up to set email alerts
|

Who painted that? The authorship of Schematic rock art at the Los Machos rockshelter in southern Iberia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similarly, more and more scientific studies are supporting the idea that it is likely that women were not so "passive" as explained in, for example, a paper by Martínez-Sevilla et al 44 A similarly recent paper questions sexist narratives about men being "natural leaders," by showing that very likely a woman occupied a highly prominent position in a major European society about four millennia ago. 45 One clear example of how sexist narratives about "coy" and "sexually passive" women still permeate current academia is that many current scientists continue to discuss what they call the "puzzle" of female orgasm (see, e.g., Pavlicev and Wagner 46 ).…”
Section: Publications and Sexismmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, more and more scientific studies are supporting the idea that it is likely that women were not so "passive" as explained in, for example, a paper by Martínez-Sevilla et al 44 A similarly recent paper questions sexist narratives about men being "natural leaders," by showing that very likely a woman occupied a highly prominent position in a major European society about four millennia ago. 45 One clear example of how sexist narratives about "coy" and "sexually passive" women still permeate current academia is that many current scientists continue to discuss what they call the "puzzle" of female orgasm (see, e.g., Pavlicev and Wagner 46 ).…”
Section: Publications and Sexismmentioning
confidence: 85%
“…Similarly, more and more scientific studies are supporting the idea that it is likely that women were not so “passive” as explained in, for example, a paper by Martínez‐Sevilla et al 44 A similarly recent paper questions sexist narratives about men being “natural leaders,” by showing that very likely a woman occupied a highly prominent position in a major European society about four millennia ago 45 …”
Section: Scientific Research Publications and Sexismmentioning
confidence: 89%
“…Fowler et al . 2020; but also see Martínez‐Sevilla et al 2020 for rock art). If we are talking about traces of marks left by human bodies, however, we ought to include here studies which have examined footprints (e.g.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Kamp et al 1999) and interrelations between craftspeople and other users of mainly ceramic artefacts (e.g. Fowler et al 2020; but also see Martínez-Sevilla et al 2020 for rock art). If we are talking about traces of marks left by human bodies, however, we ought to include here studies which have examined footprints (e.g.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Mundorff et al (2014) has identified an apparent statistic dimorphism of the breadth of the ridge of female and male fingers among modern populations. These variations have been adopted to discuss the authorship of paintings in various contexts (Martínez-Sevilla et al 2020). It has also been used to reveal children's presence and their participation in creating artwork (Kamp et al 1999 that an Aurignacian painted limestone plaque fragment from Hohle Fels in Germany has been decorated with double rows of dots stamped on with juvenile fingertips.…”
Section: Children's Participation In Creating and Viewing Rock Artmentioning
confidence: 99%